Improving Students’ Self-Esteem through Group Counseling with Assertive Training and Positive Reinforcement Techniques - Rahmat Ihtiar, Risno; Sugiyo, Sugiyo; Awalya, Awalya (Universitas Negeri Semarang, 2022)
Self-esteem is a crucial part of mental health, especially in self-acceptance. Low self-esteem is said to be a risk factor for the mental health issue development, including depression, antisocial, and low academic achievement. This study strived for examining the effectiveness of group counseling with assertive training and positive reinforcement techniques to improve students’ self-esteem. It was a quasi-experimental study with the factorial design 2x2. The study collected the data from 12 counseling sessions in group A, B, and C with the time allotment of 45 minutes for each. Self-esteem scale (SES) was the instrument used in this study. Based on Wilcoxon test, the assertiveness training positive reinforcement, and the combination of those techniques obtained similar intensity (correlated sample). In addition, the results of Two-Way ANOVA test have proved that the combination technique was the best treatment. The findings of this study can be a cognitive map for identifying students’ low self-esteem and their management on an ongoing basis.